Avaliação da presença espacial e auto presença em realidade virtual com cenários 360º: um estudo de caso com o jogo Caixa de Pandora - Carvalho, Thiago Viana de (2019)
Virtual reality technologies are capable of providing to the user a sense of presence within the virtual environment, which the importance of this construct is evidenced by the fact that the presence is capable of providing a deeper engagement of the user in the virtual environment. Knowing that serious games, games developed with a specific purpose beyond entertainment, stand out as an important application of these technologies, it is important to identify how the player’s sense of presence can be enhanced by the use of virtual reality technologies, since games are capable of generating immersion and presence through its narrative, aesthetic and mechanical elements. Based on this principle, the main objective of this work was to evaluate the player’s sense of spatial and self-presence in the context of virtual reality applied to 360º scenarios. This assessment was made from the proposal of a presence questionnaire focused on games, encompassing the previously mentioned dimensions of presence, as well as the application of this instrument in a case study with the Caixa de Pandora game (“Pandora’s Box”, in English), an educational serious game addressing the issue of violence against women. Thus, from the development of a prototype using 360º scenarios with the conceptual basis of the aforementioned game, and the subsequent application of the experiment with users, both for the original version and for the developed prototype, it was intended to identify whether the approach with 360º scenarios resulted in an improvement in these two types of presence, compared to the conventional approach. Through the obtained results, it was possible to identify a statistically significant gain in the player’s sense of spatial presence, particularly concerning immersion, involvement and realism. This gain was not observed in the player’s sense of self-presence, since there is no incorporation or identification of the player with the characters in the scene. Furthermore, the feedback of the players not only showed aspects of improvement with regard to the game design, but it was also possible to suggest guidelines for the development of 360º scenarios, involving technical aspects, as well as aesthetic and interactional elements, so that the player can get more deeply involved in the virtual environment.